EL EMPLEO SISTEMÁTICO DEL INTERNET Y LA GESTIÓN DEL CONOCIMIENTO EN LAS ENTIDADES DE CAPACITACIÓN EN TELECOMUNICACIONES DE LIMA: MODELO PROPUESTO - Vigo Sánchez, Edwin Augusto (2012)
The research focuses on the knowledge that flows in telecommunication training entities that can be capitalized using technological tools. The investigation has been made in three academic organizations related to telecommunications: a public university, a private university and an institution of higher education located in Lima-Peru. The phase of data collection has considered the planning, elaboration and application of cards of observation and interviews with professionals, professors and students of institutions. The research results have shown that the systematic use of the Internet and the knowledge management, through the degree of use of Internet and technological tools and the level of facilities for the generation and transfer of knowledge significantly improve the level of effectiveness in the management of the organizations of telecommunication training institutions of Peru and have a positive impact in the graduated professionals.